2016
DOI: 10.1099/ijsem.0.001553
|View full text |Cite
|
Sign up to set email alerts
|

Proposal to reclassify Roseivirga ehrenbergii (Nedashkovskaya et al., 2008) as Roseivirga seohaensis comb. nov., description of Roseivirga seohaensis subsp. aquiponti subsp. nov. and emendation of the genus Roseivirga

Abstract: The genus Roseivirga currently includes five species: Roseivirga ehrenbergii, R. echinicomitans, R. spongicola, R. marina and R. maritima. Marinicola seohaensis SW-152T was renamed as Roseivirgaseohaensis SW-152T and then reclassified again as a later heterotypic synonym of R. ehrenbergii KMM 6017T. In this study, based on average nucleotide identity and digital DNA-DNA hybridization values obtained from in silico methods, together with fatty acid analyses and biochemical tests, we propose to reclassify R. ehr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…In F/2 medium supplemented with sonicated diatoms, Cl-1 and Cl-8 needed at least four days, while Cl-2 needed at least seven to be detectable by qPCR, whereas little to no growth was observed in supplemented marine broth. This differs to what is present in the literature regarding the genus closest to Cl-1 [30] and Cl-8 [53][54][55][56][57], which were isolated and maintained on marine agar and marine broth, while all our attempts to culture Cl-8 on marine agar medium (including supplementation with diatom organic matter) were unsuccessful. This preference for diatom organic matter and their major distribution in the SA fraction of a classical diatom culture supports their dependence on molecules produced by the diatoms or the existence of a mutualistic relationship.…”
Section: Discussioncontrasting
confidence: 91%
“…In F/2 medium supplemented with sonicated diatoms, Cl-1 and Cl-8 needed at least four days, while Cl-2 needed at least seven to be detectable by qPCR, whereas little to no growth was observed in supplemented marine broth. This differs to what is present in the literature regarding the genus closest to Cl-1 [30] and Cl-8 [53][54][55][56][57], which were isolated and maintained on marine agar and marine broth, while all our attempts to culture Cl-8 on marine agar medium (including supplementation with diatom organic matter) were unsuccessful. This preference for diatom organic matter and their major distribution in the SA fraction of a classical diatom culture supports their dependence on molecules produced by the diatoms or the existence of a mutualistic relationship.…”
Section: Discussioncontrasting
confidence: 91%
“…As in the GBDP tree, the 16S rRNA gene trees and the ULT (Supplementary Data Sheet 1) showed Ekhidna lutea in a clade together with Marinoscillum (Seo et al, 2009) and Reichenbachiella (Nedashkovskaya et al, 2005f; Cha et al, 2011), which suggests the classification of these three genera into a new family, which is not precluded by their phenotype (Supplementary Table 1). Roseivirga (Nedashkovskaya et al, 2005a,e, 2008a; Selvaratnam et al, 2016) formed a strongly supported clade together with Fabibacter (Lau et al, 2006a), with which it was even intermixed as discussed below. The two genera are best placed in a separate family, Roseivirgaceae fam.…”
Section: Resultsmentioning
confidence: 95%
“…Roseivirga (Nedashkovskaya et al, 2005a,e, 2008a; Selvaratnam et al, 2016) appeared as polyphyletic in the GBDP tree (Figure 3) because R. spongicola was placed within a paraphyletic Fabibacter (Lau et al, 2006a). In the study that proposed both Fabibacter and R. spongicola (Lau et al, 2006a), a 16S rRNA gene tree showed F. halotolerans placed together with two environmental isolates as sister group of a Roseivirga clade that included R. spongicola but support for this arrangement was moderate and apparently only obtained in a neighbor-joining analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are equipped with adaptive mechanisms to survive in harsh osmotic conditions [ 2 , 3 , 4 , 5 , 6 ]. Halophilic microorganisms can be found in coastal and open ocean environments such as marine waters, saline lakes, and mangrove forests [ 7 , 8 , 9 , 10 ]. Mangrove forests contain plants that grow at the interface between land and sea [ 11 ] and are one of the world’s most extensive reservoirs of naturally sequestered carbon, accounting for 30% of blue carbon stored [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%